Disruption of retinol saturase enhances Polyunsaturated Fatty Acid (PUFA) biosynthesis in grass carp (Ctenopharyngodon idella) via upregulation of fads2 - Ru Zhang; Ran Yang; Jiang Zeng; Xiao Xiao; Houpeng Wang; Yongming Li; Xiaosi Wang; Jian Gao; Mudan He; Yonghua Sun (Aquaculture, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Turbulence-induced detachment of fine particles from bubble surfaces and associated flow field characteristics - Hailing He; Zhixin Sun; Xiaoheng Li; Xiaokang Yan; Lijun Wang; Haijun Zhang; Li Lin; Jincai Ran (Minerals Engineering, 2026)

Lipid-lowering activity of mulberry seed unsaturated fatty acids: integrating network pharmacology and experimental validation - Yue Zhang; Haoran Huang; Jianglong He; Yuqi Li; Xueping Jiang; Ping Wu; Syed Asim Shah Bacha; Ran Zhang; Hao Li; Gaiqun Huang; Zhongzheng Gui (Functional & Integrative Genomics, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Long-term nitrogen deposition weakens the CH4 sink capacity, but enhances the CO2 and N2O source potential of the alpine grassland soil - Hang Shi; Xiaoqing Cui; Shikui Dong; Zilong Liu; Ran Zhang; Ke Zhang; Xueqi Li; Yuhao Zhang; Hui Zuo; Fengcai He; Xianqi Zhou; Mingjie Ran; et al. (Agriculture, Ecosystems & Environment, 2026)

Synergistic effects of lipid degradation and the Maillard reaction: Decoding the flavor formation of charcoal-grilled lamb skewers based on flavoromics, sensomics, metabolomics, and lipidomics - Che Shen; Xinyu Jiang; Jiajin Sun; Meiyi Li; Ran Wang; Yunhui Zhang; Jing Tian; Lizhang Wu; Xiongfeng He; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Biomass carbon dots and oxidized anthocyanins dual-driven strategy: enhanced collagen films for shrimp preservation and colorimetric/fluorescent freshness monitoring - Linjing He; Ruimin Ran; Feizhi Li; Wenli Shi; Yeqing He; Hengjun Xiang; Guoying Li (Food Research International, 2026)

Cyanidin chloride activates mitophagy to delay aging via PINK1/parkin pathway - Zhaotun Hu; Yan Ran; Xiaocong Li; He Zha; Yi Xiao (Food Research International, 2026)

Limited enzymatic hydrolysis-mediated assembly of whey protein isolate nanofibers: Influence of protease type and hydrolysis time on fiber formation and β-carotene delivery - Shudong He; Yanni Wu; Tong Jin; Qiming Li; Tianjiao Niu; Xiaodong Cao; Ran Xiao; Hanju Sun; Walid Elfalleh (Food Chemistry, 2026)

Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Improving extreme runoff simulation with spatially optimized Fengyun satellite precipitation - Yuehua Ran; Kunlong He; Xiaohong Chen; Haojie Li (Journal of Hydrology, 2026)

Effects of organic material addition on yield, nitrogen use efficiency, soil properties and physiological traits of grain crops: A meta-analysis - Feiyang He; Yaru Pang; Yueshan Song; Ran Xu; Daoyin Shi; Yisha Yang; Yapeng Li; Jiali Yang; Guorui Li; Weiyan Wang; Pengfei Shen; Xiaoxia Wen (European Journal of Agronomy, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

Peak greening at moderate shrinking intensity across Chinese counties - Ran Chen; Wenxiao Jia; Kai Wang; Xinyuan Zhang; Jiaxuan Xin; Wenjian Li; Zhijun Zhang; Junling He (Journal of Environmental Management, 2026)

Food-microbiota interactions in the oral cavity: A comprehensive review of how food compositions affect oral microbiota homeostasis and oral health - Siyu Chen; Xiaohan Zhang; Yuan Liu; Ran Wang; Tongtong Chen; He Li; Xinqi Liu; Chi Zhang (Trends in Food Science & Technology, 2026)

Ferrocene-MOF derived nanoporous carbon for magnetic solid-phase extraction of p‑phenylenediamine antioxidants and quinone-derivatives in various environmental water samples - Jia-Qi Zhao; Bing-Dan Wang; Ao-Ran Wang; Yu-Tian Cai; Shou-Fang Jiang; Hai-Jie Li; Yu He; Man-Man Wang (Journal of Hazardous Materials, 2026)

The saturation degree of dietary fatty acids alters the phenotypes of lipoprotein subclasses and plasma metabolome in piglets - Ying Li; Yajie Wang; Ran Ma; Zhihua Li; Zemeng Feng; Xiangfeng Kong; Qian Zhou; Xiaoming Guo; Yulong Yin; Yongning Wu; Qinghua He (Food Chemistry, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Beyond magnetic-field enhanced peroxymonosulfate activation: Interfacial restructuring of nanoscale Fe0 for efficient contaminant degradation - Jingyang Luo; Ran Yu; Xinyi Liu; Chao He; Fuqiang Liu; Jianglei Xiong; Shilong Jiang; Song Cheng; Yiping Li (Chemical Engineering Journal, 2026)

GIS-based Geotourism Route Design in Changbaishan Global Geopark - Junbo Zhao; Jinxin He; Jian Yi; Xiangjin Ran; Jiaming Li (Geoheritage, 2026)

Gene Rearrangement in the Mitochondrial Genomes of the Sand Crabs Albunea symmysta (Anomura:Hippoidea) with Insights into Phylogenetic Relationships in the Anomura (Crustacea: Decapoda) - Bin Li; Jichun Li; Jie He; Suzhen Ran; Jianshe Zhang; Alexei V. Chernyshev; Jiji Li; Yingying Ye (Biochemical Genetics, 2026)

Genome wide association analysis and association of genetic risk and lifestyle with upper gastrointestinal cancer among an endoscopy-screened cohort in China - Feifan He; Xianhui Ran; Hao Jiang; Zhiyuan Fan; Yueying Zhang; Jinwu Wang; Changqing Hao; Guohui Song; Yanwei Gong; Yanyan Li; Xinqing Li; Ru Chen; et al. (Science Bulletin, 2026)

Unveiling the hidden threat of chlorinated organic pollutants residual in anaerobic conditions: A regional multi-habitat perspective - Shuyao Li; Yifan Song; Ran Bao; Wei Wang; Jiachun Shi; Chaofeng Shen; Jianming Xu; Yan He (Journal of Hazardous Materials, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Pollution characteristics of Litopenaeus vannamei greenhouse effluents and purification performance of a combined flocculation–ecological floating bed system - Shanyuan Xue; Guo Li; Ensheng Zhu; Weizhen Zhang; Jiao Ran; Zhe Li; Yu Zhao; Jingru Hu; Jing Dong; Yingxue Yi; Dan Zhou; Qiang He; et al. (Journal of Environmental Chemical Engineering, 2026)

Pulsed ultrasound-assisted deep eutectic solvent-mediated stabilization and bioactivity enhancement of hydrolysable tannins from chestnut (Castanea mollissima) burrs - Xingying Xue; Zhiwen Qi; Hao Zhou; Ran Tao; Wenjun Li; Qin He; Jiandu Lei; Chengzhang Wang (Food Research International, 2026)

Collagen films enhanced with bovine hide-tannic acid carbon dots: A traditional tanning-inspired strategy for crispy fried chicken preservation - Linjing He; Ruimin Ran; Xin Guo; Wenli Shi; Zhijie Zhang; Guoying Li (Food Hydrocolloids, 2026)

Experimental and numerical research on the seismic performance of novel UHPC columns - Ye He; Xin Nie; Jiansheng Fan; Yueyi Li; Ran Ding (Engineering Structures, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Facet-engineered Fe-Ni/CeO2 catalysts for selective CO2-assisted oxidative dehydrogenation of ethane - Xiuquan Li; Haonan Niu; Zhongqing Yang; Ziqiang He; Ruiming Fang; Jiang He; Ziqi Wang; Kadirova ZC; Jingyu Ran (Fuel, 2026)

Bioinspired lignin-based coatings for durable and photothermal antibacterial surfaces - Cheng Wang; Bowen Ran; Kexin Li; Xiaodong He; Jing Li; Yunjie Xiang; Kun Xu; Xi Rao; Selvakumar Murugesan; Valentim A.R. Barão; En-Tang Kang; Liqun Xu (Chemical Engineering Journal, 2026)

Continuous adjoint optimization method for building fluid systems based on mesh-adaptive deformation with a low deformation rate relaxation mechanism - Yingying Wang; Ruoyin Jing; Nan Li; Ran Gao; Ao Tian; Junkai Ren; Yibu Gao; Shu He (Building and Environment, 2026)

Global research trends and future directions for Janus kinase inhibitors in rheumatoid arthritis: a comprehensive bibliometric analysis - Xiaonan Yang; Huixian Gao; Wenhao Zhang; Ran Li; Xue He; Huan Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Safe nitrogen boundaries for sustainable pomelo production: A case study in the hilly regions of southern China - Ziwei Luo; Ran Li; Xiaotong Hu; Yedong Liu; Zhiyuan He; Ruixiang Yang; Zhixiong Zeng; Yingzhe Zeng; Bingkun Lu; Xiaojun Yan; Liangquan Wu (Agriculture, Ecosystems & Environment, 2026)

A multifunctional 5-fluorouracil prodrug: synthesis, biological evaluation, and antitumor mechanism investigation - Ran Zhang; Liqing Tang; Jianglong He; Guanyu Jiang; Yingfei Su; Xueping Jiang; Ping Wu; Dongyang Zhang; Sitong Chen; Hao Li; Zhongzheng Gui (Molecular Diversity, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Tempol suppresses ferroptosis and relieves chronic intermittent hypoxia-induced lung injury through the inhibition of TLR4 and activation of the Nrf2/GSH axis - Ran Li; Ruiting Qin; Zhijuan Liu; Xiaojie He; Dan Li; Li Ai (Tissue and Cell, 2026)

DNMT1-mediated LAMA2 inhibition induces M2 macrophage polarization during prostate cancer progression - Ruiqian Li; Chen Hu; Fengming Ran; Yu Bai; Hongyi Wu; Wenjun Peng; Yixuan He; Qilin Wang; Jun Li (Tissue and Cell, 2026)

Hierarchical carbon electrocatalysts with atomic Co-N/Pyridinic-N synergy for efficient bifunctional oxygen reactions - Jian Li; Zongqi Zhao; Xinxin Pi; Guangshun Chai; Lingtao Ran; Chunlei Zhang; Yanhui Li; Junhan He; Keke Zhang; Yan He (Fuel, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Manipulating starch crystalline structure for controlled digestibility and glycemic response - Ruixin Zhu; Xiaoxia Li; Jiale Ren; Pengjie Wang; Ran Wang; Jie Guo; Jingjing He; Jiayue Guo; Siyuan Liu; Fazheng Ren; Hao Xu; Yao Hu (Carbohydrate Polymers, 2026)

Molecular Responses of Cold Stress Adaptation in the Red Grouper (Epinephelus Akaara): Compensatory Regulation Between FOXO and MAPK Signaling Pathways - Bin Li; Jichun Li; Hongling Ping; Tao Zhang; Jie He; Suzhen Ran; Jianshe Zhang; Xiaolong Yin; Yingying Ye; Huilai Shi; Jiji Li (Marine Biotechnology, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

High-Fidelity Morphological and Mineralogical Reconstruction of Chang’E-5 Lunar Regolith Grains - Quan Zheng; Ziwei Tian; Songzheng Yu; Ronghua Pang; Guang Zhang; Guanghui Liu; Yiwei Liu; Yang Li; Xin Liu; Shijing He; Ran Niu; Peng Zhang (Computers and Geotechnics, 2026)

Deprotonation-triggered rapid gel coating: Liposome encapsulated luteolin /chitosan enabling dual sustainable food preservation and damage resistance - Wenli Shi; Ruimin Ran; Xin Guo; Linjing He; Guoying Li (Chemical Engineering Journal, 2026)

Fixed-Time Preset Performance Sliding Mode Control for Underwater Manipulators Considering Input Saturation - Ran Wang; Weiquan Huang; Zixuan Li; Yanjie Song; He Wang (Journal of Marine Science and Engineering, 2025)
This paper addresses the trajectory tracking problem for a six-degree-of-freedom (6-DOF) underwater manipulator subject to complex disturbances and input saturation. It proposes a fixed-time preset performance sliding mode control method considering input saturation (FT-PP-SMC-IS), aiming to achieve rapid and stable tracking performance under these constraints. Firstly, to improve modeling accuracy, the Newton–Euler method and Morison’s equation are integrated to establish a more precise dynamic model of the underwater manipulator. Secondly, to balance dynamic and steady-state performance, a preset performance function is designed to constrain the tracking error boundaries. Based on dual-limit homogeneous theory, a fixed-time sliding mode surface is constructed, significantly enhancing the convergence speed and fixed-time stability. Furthermore, to suppress the effects of input saturation, a fixed-time auxiliary system is designed to compensate in real-time for deviations caused by actuator saturation. By separately constructing the sliding mode reaching law and equivalent control law, global fixed-time convergence of the system states is ensured. Based on Lyapunov stability theory, the fixed-time stability of the closed-loop system is rigorously proven. Finally, comparative simulation experiments verify the effectiveness and superiority of the proposed method.

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

The detection method of ammonia nitrogen concentration in water bodies based on hyperspectrum - Yahe Di; Tao Li; Hui Ran; Rui Yang; Fei He; Aixuan Li; Chenzhan Tang; Wenjing Tian (Journal of Water Process Engineering, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Strong carbonate buffering in karst cascade river-reservoir systems constrains CO2 production and emissions - Xuan Hu; Wanfa Wang; Lishan Ran; Sen Xu; Qiong Han; Francesco Ulloa-Cedamanos; Jun Zhong; Bei-Bei Chen; Shengde Yu; Dengming He; Wenhong Shi; Siqin Xu; et al. (Geochimica et Cosmochimica Acta, 2025)

Development of a dual-layer collagen film with insulating, antioxidant, antimicrobial, and pH-sensitive properties for the maintenance and visual monitoring of shrimp freshness - Ruimin Ran; Xiaoyun Luo; Dongmei Zhai; Yeqing He; Xin Guo; Linjing He; Guoying Li (Food Hydrocolloids, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Stirring enrichment/bio-proliferation dual-amplified photoelectrochemical phage biosensor for selective and sensitive detection of foodborne pathogens - Yuqi Zhang; Liu Liu; Tianhua Li; Rouyi Gao; Wenhao Dong; Yan Bai; Lingman Ran; Suying Gu; Zhenzhong Yu; Jincan He; Ning Gan (Analytica Chimica Acta, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Unraveling mulberry anthocyanins’ antioxidant mechanism and biosafety via computational modeling - Jianglong He; Yuqi Li; Xueping Jiang; Haoran Huang; Yue Zhang; Ran Zhang; Hao Li; Zhongzheng Gui (Food Bioscience, 2025)

P38 MAPK regulates phagocytosis of bacteria and fungi by hemocytes in Macrobrachium rosenbergii - Ran Geng; Bangping Hu; Alian Liao; Lingling Li; Hongliang Zuo; Zhixun Guo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Lipidomic profiling of cutaneous surface lipid alterations in sensitive scalp in Beijing - Ran Li; Qian Jiao; Liya Song; Youjie He; Huaming He; Cheng Zhou; Yan Jia (Chemistry and Physics of Lipids, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Comparative DFT study on the reaction mechanism of dry reforming of methane over Ni (111), Ni@Co (111) and Co (111) surface - Zhiliang Ou; Qingsong Zuo; Ziqiang He; Kai Wang; Wenpin Zhang; Xiuquan Li; Jing Liang; Ying Chen; Jingyu Ran (Fuel, 2025)

Elucidating the mechanism of dibutyl phthalate on Alzheimer's disease through network toxicology, molecular docking and validation in mouse neuroblastoma cells - Jing Zi; Xinlong Li; Qianqian Cao; Yifan Hu; Zhichang Ran; Yanliu Li; Jiayuan He; Xiaoyu Wang; Guo Cheng; Jingyuan Xiong (Food and Chemical Toxicology, 2025)

Impact of system size on pattern transitions in dissolving rough fractures: experiments, multi-physics coupling simulations and theoretical analysis - Ting Wang; Yaning He; Yanlong Li; Ran Hu; Yang Zhou; Yifeng Chen; Junrui Chai; Yunhe Liu (Computers and Geotechnics, 2025)

High humidity-resisted all-wood-based triboelectric nanogenerator for energy harvesting and human motion monitoring - Peiyao He; Xiaojun Li; Min Wang; Dong Lv; Jingqiu Wang; Linjun Zou; Ruixiang Cheng; Ran Yin; Xiang Chi; Jian Li; Likun Gao (Chemical Engineering Journal, 2025)

Grazing mediates soil nutrient stocks through changing the plant functional composition and plant biomass allocation in alpine grassland - Fengcai He; Shikui Dong; Chunhui Ma; Xinghai Hao; Hao Shen; Juejie Yang; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

A study on the impact of digitalization on green agricultural development and its spatial effects in China - Xiaowen Dai; Yao Li; Ying Qi; Yi Chen; Yanqiu He; Ruiping Ran; Qi Yin (Environment, Development and Sustainability, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Decoding soil carbon and nitrogen dynamics: The integrated role of biotic and abiotic drivers in subtropical forests - Jie Gao; Songlin Zhang; Yuanyuan Wu; Xinrui He; Yiji Xu; Xiaolin Liu; Yangyi Chen; Junchen Liu; Qiong Ran; Changxiao Li (CATENA, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

A Framework for Mining Intercity Relationship of PM2.5 Based on Granger Causality Test: Application to Cities in China - Ran-Ran He; Dong-Qin Li; Sun Zhang (Environmental Modeling & Assessment, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Rotational grazing can enhance the soil available nutrients rather than plant diversity to promote ANPP of alpine steppe - Fengcai He; Shikui Dong; Juejie Yang; Xinghai Hao; Chunhui Ma; Hao Shen; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Transcriptome Analysis Reveals Hyperglycemic Hormone and Excitatory Amino Acid Transporter 3 Are Involved in the Thermal Adaptation of Eriocheir sinensis - Xi Li; Runlin Zhou; Ruiqi Zhang; Zhen He; Mingzhi Zhang; Ran Li; Tong Hao; Jinsheng Sun (Fishes, 2025)
Temperature is one of the critical factors influencing the survival, growth, and reproduction of organisms. The molting and developmental mechanisms of crustaceans are highly sensitive to temperature, yet the regulatory mechanisms underlying their thermal adaptation remain unclear. In this work, transcriptome sequencing was performed to analyze the gene expression profiles of Eriocheir sinensis under normal temperature (22 °C) and high-temperature (27 °C and 32 °C) conditions. A total of 377 differentially expressed genes (DEGs) were identified, including 149 up-regulated and 227 down-regulated genes. Through Gene Ontology (GO) enrichment analysis of these DEGs, 11 significantly temperature-regulated signaling pathways were identified, including the estrogen and androgen receptor signaling pathways, and two neurotransmission signaling pathways. These findings suggest that temperature may influence sex regulation in E. sinensis, while the dopamine receptor and neuropeptide signaling pathways may play a role in its thermal adaptation. Further validation via RT-qPCR of DEGs involved in neurotransmission signaling pathways revealed that crustacean hyperglycemic hormone (CHH) and excitatory amino acid transporter 3 (EAA3) genes are likely involved in the thermal adaptation of E. sinensis. In addition, the hemolymph glucose levels associated with the elevated temperatures were detected and consistent variations between glucose levels and CHH expressions were found. This indicates that the eyestalk CHH is strongly correlated with the hemolymph glucose levels and likely mediates the response to temperature changes by regulating blood glucose in E. sinensis. The results of this study not only provide key molecular targets for elucidating the mechanisms by which temperature affects molting and development in E. sinensis, but also establish a theoretical foundation for further research into thermal adaptation strategies in crustaceans.

China’s marine plastic pollution governance path: focusing on the judicial positioning of PIL initiated by procuratorial agencies - Ben-Chao Fu; Chuan-Kai Guo; Xiu-Juan Li; Hai-Dong Cai; Jin-Hua Guo; He-Ran Li (Frontiers in Marine Science, 2025)
Can procuratorial agencies play a key role in China’s governance of marine plastic pollution (MPPG)? Within the current discussions about the legal framework of China’s MPPG, courts, marine environmental regulatory authorities, procuratorial agencies, and environmental protection organizations are typically seen as the main stakeholders. However, the role of procuratorial agencies, as the statutory entity for initiating PIL in marine environmental protection, has been significantly overlooked. This raises a range of questions including how should procuratorial agencies leverage their advantages in PIL to enhance the diversity of participants in the litigation process? What inherent challenges exist in marine environmental lawsuits? What substantive and procedural obstacles will procuratorial agencies face when engaging in MPPG-related litigation? This study argues that procuratorial agencies, by fulfilling their public interest litigation (PIL) function in marine environmental protection, can effectively improve MPPG governance. The study focuses on issues such as the unclear prerequisites for initiating MPPG-related lawsuits by procuratorial agencies, the criteria for selecting diverse litigation models, and the applicability of procuratorial agencies’ PIL in foreign-related cases.

Experimental and numerical simulation analyses of a displacement-dependent self-centering variable friction damper - Ran Li; Qifeng Chen; Yuhang He; Shitong Chen; Hanbin Ge (Soil Dynamics and Earthquake Engineering, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

An ultra-sensitive, intelligent platform for food safety monitoring: Label-free detection of illegal additives using self-assembled SERS substrates and machine learning - Chunjuan Yang; Shuang Jiang; Yue Zhao; Li Zhang; Xiaoming Lyu; Shulu Zhang; Jiayue Liang; Yiyang He; Xubin Quan; Mingxu Zhang; Ran Gao; Renxing Song; et al. (Food Chemistry, 2025)

Active chitosan films crosslinked by vanillin-derived dialdehyde for effective fruit preservation - Ran Li; Zeqi Liu; Juan Guo; Wenbo Xu; Xuan Ning; Xiaojun Li; Meng He; Qingye Liu (Food Hydrocolloids, 2025)

Corrigendum to “Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration” [Chem. Eng. J. 450 (2022) 138291] - Meixin Ran; Yaxin Deng; Jiaqi Yan; Anan Zhang; Ying Wei; Xiaowen Li; Haibing He; Jingxin Gou; Tian Yin; Xing Tang; Jun Kong; Han Zhang; et al. (Chemical Engineering Journal, 2025)

An in-situ gold growth self-catalytic signal amplification system enhanced hollow gold immunochromatography for ultrasensitive detection of p24 antigen in HIV infection - Chuanjiang Ran; Qingjie Zhang; Zhenglin Long; Yuhao Li; Xinyue He; Shengzhou Li; Chen Chen; Cong Cheng; Ying Xu; Wenli Zhang; Wei Guo; Yan Shen (Chemical Engineering Journal, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Impact of ultrasonication on the regeneration of tetracycline-saturated activated carbon and activated coke using persulfate - Xiao Mi; Dongyang Ren; Guobiao He; Yuming Cui; Gangfu Song; Baogui Wang; Yingxu Liu; Yunlong Ran; Tannaz Pak; Guoting Li (Journal of Environmental Chemical Engineering, 2025)

Water solubility in nominally anhydrous minerals in a silica-rich system at the top lower mantle - Luyao Chen; Zhaodong Liu; Xinyu Zhao; Chaowen Xu; Dongyang Ju; Bingtao Feng; Jinze He; Ran Liu; Xinyang Li; Wei Du; Bingbing Liu; Wenliang Xu (Earth and Planetary Science Letters, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Pillar[5]arene@AuNP-Functionalized, Magnetically-Propelled Helical Micromotors for On-The-Fly Electrochemical Biosensing of p53 DNA Sequence - Zhiyong Ran; Yue Li; Xiankun Lin; Qiang He (Chemical Engineering Journal, 2025)

Short-term P addition weakens the positive effects of N addition on CH4 uptake in alpine grasslands of the Qinghai-Tibetan Plateau - Jiannan Xiao; Shikui Dong; Hao Shen; Ran Zhang; Hang Shi; Fencai He; Wei Li; Xiaoyan Li (Plant and Soil, 2025)

Pueraria thomsonii Benth-Associated Endophytes: A Multifaceted Exploration of Its Bioactive Molecules - Yu Li; Yu Liu; Yalan Ran; Shiqin Peng; Xiaoman Yuan; Lingyun Zhao; Huiru Sun; Fulian Su; Donghai Huang; Saravana Kumar Pachaiyappan; Meijun He (Indian Journal of Microbiology, 2025)

Evaluation of Geosites in Changbaishan Global Geopark based on Fuzzy AHP and TOPSIS - Jiaming Li; Jinxin He; Peng Lu; Xiangjin Ran; Jian Yi (Geoheritage, 2025)

Comparison and mechanism analysis of fatty acid differences between backcross F2 derived from blunt snout bream (Megalobrama amblycephala,♀) × topmouth culter (Culter alburnus,♂) and its closely related species - Qixiang Wang; Haoyang Wangchen; Junhan Luo; Yanling Qing; Ran Jiang; Yanan Luo; Xing Gao; Jing Liu; Zhenfeng Chen; Yanfang Li; Shenping Cao; Jianzhou Tang; et al. (Aquaculture International, 2025)

Global Fast Terminal Sliding Mode Control of Underwater Manipulator Based on Finite-Time Extended State Observer - Ran Wang; Weiquan Huang; Junyu Wu; He Wang; Jixiang Li (Journal of Marine Science and Engineering, 2025)
This study investigates the trajectory-tracking control problem of a two-degree-of-freedom underwater manipulator operating in a complex disturbance environment. A dynamic model of the multi-link serial manipulator is first established. In this study, water resistance and additional mass forces acting on the manipulator are analyzed and calculated using differential analysis and the Morrison formula. To account for coupling between joints, the concept of equivalent gravity is introduced to precisely calculate the underwater manipulator’s buoyancy and gravity. As a result, a relatively accurate dynamic model of the underwater manipulator is established. To mitigate the influences of external disturbances and unmodeled parts on the manipulator, a finite-time extended state observer (FTESO) is designed to estimate system quantities that are difficult to measure directly. The robustness of the controller is enhanced using a feedforward compensation mechanism, and it is demonstrated that the observation error of the observer converges in finite time. Finally, a global fast terminal sliding mode controller (GFTSMC) is developed for trajectory tracking, integrated with the aforementioned observer, and designed to smooth and limit the controller’s output. The controller’s stability is proven using Lyapunov stability theory, and its effectiveness is verified through simulation-based comparison experiments.

Pore microstructure and mass transfer dynamics in thick electrodes for high energy density lithium-ion batteries - Bowei Li; Shanfeng Wang; Pan He; Zhenyao Huang; Bo Mai; Xia Zhang; Yuhang Chen; Yuehua Wen; Xiaqing Ran; Chunhua Han; Ingo Manke; Kang Dong; et al. (Chemical Engineering Journal, 2025)

Predicting Persistent Aneurysm Filling After Pipeline Embolization Device Treatment in Patients with Intracranial Aneurysm: Development and External Validation of a Nomogram Model - Linggen Dong; Chao Wang; Xiheng Chen; Mingtao Li; Tong Li; He Liu; Yang Zhao; Ran Duan; Weitao Jin; Yukun Zhang; Yang Wang; Ming Lv (Translational Stroke Research, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Quantitative source apportionment and health risk assessment for polycyclic aromatic hydrocarbon and their derivatives in indoor dust from housing and public buildings of a mega-city in China - Jijie Kong; Sirui Yan; Xiaoyu Cao; Yuteng Zhang; Chengling Ran; Xianxian Chen; Shaogui Yang; Shiyin Li; Limin Zhang; Huan He (Journal of Hazardous Materials, 2025)

Mechanisms of soybean proteins and peptides regulating the adhesion of Lacticaseibacillus rhamnosus GG and Lactiplantibacillus plantarum K25 to intestinal cells: A Comparative Study - Yinxiao Zhang; Yanchao Wen; Chi Zhang; Yuan Liu; Ran Wang; He Li; Xinqi Liu (Food Bioscience, 2025)

Development of multi-functional collagen films for maintaining and visually monitoring shrimp freshness - Ruimin Ran; YeQing He; Xiaoxia Zhang; Xingling Zeng; Xin Guo; Xiaoyun Luo; Guoying Li (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The time-stamped effects of screen exposure on food intake in adults: A meta-analysis of experimental studies - Jing Bai; Hao Zhu; Xiaowen Ran; Haiyan Qu; Li He; Yang Zhao (Appetite, 2025)

Water-soluble sulfur quantum dots as a potential sensitive fluorescent probe for quercetin detection and cell imaging - Weijia Jiang; Ran He; Feng Zhang; Li Wang; Yanli Wei (Food Chemistry, 2025)

Two birds with one stone: Alleviating copper toxicity and inhibiting its upward transport in non-host rice (Oryza sativa L.) by inoculation of Cu-resistant endophytes from the hyperaccumulator Commelina communis - Maodi Ran; He Li; Ying Jiao; Jiaokun Li (Environmental Pollution, 2025)

Flooding increases plant-derived carbon accumulation in soils of aquatic-terrestrial ecotone - Yiguo Ran; Ziqiang Mao; Hanzhong Jia; Xianjing He; Shaopan Xia; Fei Ye; Chamindra L. Vithana; Siyue Li; Shengjun Wu; Ping Huang (Journal of Environmental Management, 2025)

Characterization of ornithine decarboxylase with histidine decarboxylase activity in natural histidine decarboxylase gene deletion Enterobacter hormaechei RH3 - Huijie Pei; Yilun Wang; Wei He; Yue Zhang; Lamei Yang; Jinhai Li; Yixuan Ma; Xinjie Hu; Shuhong Li; Jianlong Li; Kaidi Hu; Aiping Liu; et al. (Food Microbiology, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

Dose–response effects of caffeine during repeated cycling sprints in normobaric hypoxia to exhaustion - Yinhang Cao; Wei He; Li Ding; Tze-Huan Lei; Zachary Schlader; Toby Mundel; Ran Wang; Li Guo; Jue Liu; Olivier Girard (European Journal of Applied Physiology, 2025)

Refined one-dimensional modeling and experimental validation of scroll compressor with vapor injection for electric vehicles - Kang Li; Jiayun Hu; Chao Li; Xuejin Zhou; Ni Liu; Hua Zhang; Binlin Dou; Qize He; Ran Tu; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Sustainable soil rehabilitation with multifunctional mandarin orange peel/tobermorite composite hydrogels: Water retention, immobilization of heavy metals, fertilizer release and bacterial community composition - Caiqing He; Xugang Wang; Haiyan Mou; Wenjing Hou; Qilu He; Yuchen Kang; Hao Kong; Ran Li; Wenqing Chen; Tianqi Ao; Shuanjun Li; Jian Yang; et al. (Chemical Engineering Journal, 2024)

Nanoscale Biochar for Fertilizer Quality Optimization in Waste Composting: Microbial Community Regulation - Ran Tao; Menghan Cui; Yuqing Li; Jixiang Wang; Weijiang He; Yingjie Zhao; Wenping Xie; Yu Shen; Yanfang Feng; Jason C. White (Bioresource Technology, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Voluntary walking related joint movement training with targeted epidural electrical stimulation enabled neural recovery for individuals with spinal cord injury - Xi Zhang; Yang Lu; Boyang Zhang; Hongda Li; Qingyu Yao; Junhong Lim; Yunyue Wei; Kaibo He; Chenhui Zuo; Yanan Sui; Bozhi Ma; Mingshan Ran; et al. (Science Bulletin, 2024)

Charge transfer complex induced confinement effect between organic semiconductor and polymer chains for enhancing high-temperature capacitive energy storage - Tan Zeng; Chao Yuan; Qiao Li; Zhaoyu Ran; Li Meng; Jing Fu; Dongduan Liu; Jinliang He; Qi Li (Chemical Engineering Journal, 2024)

Differential scavenging behavior of anthropogenic Pb revealed by sediment traps in the northern South China Sea basin - Weiying Li; Jingjing Zhang; Hongliang Li; Shuh-Ji Kao; Zezhou Wu; Xingju He; Lihua Ran; Martin G. Wiesner; Jianfang Chen (Acta Oceanologica Sinica, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Novel visible-light activated photocatalytic ultrafiltration membrane for simultaneous separation and degradation of emerging contaminants - Ran Li; Zhidong Wei; Peng Li; Yangbo Qiu; Chengyi Wang; Chao Wang; Long-Fei Ren; Jiahui Shao; Yiliang He (Journal of Hazardous Materials, 2024)

Effect of pasteurization and storage on the bioavailability of milk proteins during in vitro intestinal digestion and Caco-2 cell transport - Xing Li; Ran Xiao; Shudong He; Yuxiang Gu; Tianjiao Niu (Food Bioscience, 2024)

Effects of Aeromonas infection on the immune system, physical barriers and microflora structure in the intestine of juvenile grass carp (Ctenopharyngodon idella) - Meixing Guo; Ran Peng; Kelan Jin; Xia Zhang; Huilan Mo; Xiang Li; Fufa Qu; Jianzhou Tang; Shenping Cao; Yonghua Zhou; Zhimin He; Zhuangwen Mao; et al. (Fish & Shellfish Immunology, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Ship Chain Navigation Co-Scheduling of Three Gorges-Gezhouba Dam under Serial-Lock Scenario - Hongwei Tian; Qianqian Zheng; Yu Zhang; Lijun He; Shun Liu; Ran Li (Journal of Marine Science and Engineering, 2024)
Motivated by the operational scenarios of lock scheduling, we propose a serial-lock chain navigation problem (SLCNP) modeled on the Three Gorges-Gezhouba Dam (TGGD) for the first time. Ship grouping, synchronized moving, and grouped waiting operations are integrated into the ship navigation process. A mixed integer programming (MIP) model that incorporates real-world constraints such as ship priority, service fairness, traffic flow equilibrium, and phased ship placement is presented to optimize ship throughput and ship stay time. To solve the SLCNP, a sort-pick strategy-based swarm intelligence algorithm (SPSSIA) framework is developed that integrates the characteristics of SLCNP through a hybrid multi-section encoding method and a two-stage heuristic decoding approach. A swarm intelligence evolution mechanism is used to improve the search ability and robustness of the framework. Several instances are generated based on real data to verify the correctness and effectiveness of the model and algorithm. Computational results demonstrate the applicability and effectiveness of the proposed SPSSIA. Further analysis of the experimental results indicates that the key impact factors significantly influence the navigational performance of the TGGD system. The results of this study will provide practical guidance for the operational processes of inland river hubs with comparable characteristics.

Chitosan-coated double-loaded liposomes as a promising delivery system for clove essential oil - Qingqing Li; Cenchen Ran; Jingya Chen; Jiaxin Jin; Jinsong He; Yangyang Li; Qingling Wang (Journal of Food Engineering, 2024)

Encapsulation of probiotic Lacticaseibacillus casei with whey protein isolate/soybean hull polysaccharide enhances cell viability in harsh conditions - Hong Song; Ran Li; Lina Yang; Shengnan Wang; Yinxu Zhang; Jun Li; Danshi Zhu; He Liu (Food Hydrocolloids, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

In situ acid production by organic matter induced with trace homogeneous Fenton reagent for membrane fouling control - Rui Miao; Haoxue Ran; Yifan Yang; Yanfei Li; Zhuowen Ma; Yongtao Lv; Xiaorong Meng; Miaolu He; Lei Wang (Water Research, 2024)

Efficient reduction of Cr(VI) by guava (Psidium guajava) leaf extract and its mitigation effect on Cr toxicity in rice seedlings - Maodi Ran; Yongqing Lu; Yanzhen Ren; Li He; Jiaokun Li (Journal of Environmental Sciences, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

Effect of soybean proteins and peptides on the growth and adhesive ability of Limosilactobacillus Reuteri DSM17938 - Yan Wang; Jingyi Wang; Yanchao Wen; Yinxiao Zhang; Ran Wang; Yuan Liu; He Li; Yan Li; Chi Zhang (Archives of Microbiology, 2024)

Study on the habitat evolution after dam removal in a habitat-alternative tributary of large hydropower station - Zhenhua Wang; Jingjie Feng; Tao He; Jiuxian Yang; Hang Wan; Yuliang Yuan; Ran Li (Journal of Environmental Management, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

Soot particles formed by n-heptane and n-heptane/oxymethylene ether-3 in an inverse diffusion flame: A comparative analysis of chemical features - Ye Liu; Ran Zhang; Jun Wang; Yajun Wang; Gang Lv; He Yang; Haibo Chen; Tiezhu Li; Bin Hao; Junhua Guo (Fuel, 2024)

Evaluation and attribution of shortwave feedbacks to ENSO in CMIP6 models - Junjie Huang; Lijuan Li; Yujun He; Haiyan Ran; Juan Liu; Bin Wang; Tao Feng; Youli Chang; Yimin Liu (Climate Dynamics, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Biodegradation of activated sludge extracellular polymeric substances as the electron donors for denitrification - Xianbao Wang; Yudi Zhang; Dong He; Jiarong Ran; Minting Zhang; Xiang Li; Jialu Zhang; Lixin Zhang; Anlong Zhang (Journal of Environmental Chemical Engineering, 2024)

A versatile AIE probe with two cross-talk-free emissions for dual detection of SO2 and viscosity and its application in food and biological imaging - Di Zhang; Min Wang; Man Li; Lin Liu; Ran Duan; Nana Xue; He Chen; Lijun Shang; Tieliang Wang; Xujin Wu; Junfeng Zhang (Food Chemistry, 2024)

Dynamic response mechanism and precursor characteristics of gneiss rockburst under different initial burial depths - Dongqiao Liu; Jie Sun; Wen Meng; Manchao He; Chongyuan Zhang; Ran Li; Binghao Cao (Journal of Mountain Science, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Estimation of sequential transient flow around cylinders using recurrent neural network coupled graph convolutional network - Hao-Ran Xie; Yue Hua; Yu-Bai Li; Nadine Aubry; Wei-Tao Wu; Yong He; Jiang-Zhou Peng (Ocean Engineering, 2024)

LSTM time series NDVI prediction method incorporating climate elements: A case study of Yellow River Basin, China - Yan Guo; Lifeng Zhang; Yi He; Shengpeng Cao; Hongzhe Li; Ling Ran; Yujie Ding; Mikalai Filonchyk (Journal of Hydrology, 2024)

High fat diet-induced downregulation of TRPV2 mediates hepatic steatosis via p21 signalling - Pengfei Wei; Lixuan Li; Chenqiu Ran; Mingyue Jin; Huijuan Zhao; Kelaier Yang; Yu Wang; Huaqiu He; Mengyang Jia; Hongyan Pan; Qiang Li; Jing Guo (Journal of Physiology and Biochemistry, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Inclined rigid sliding walls to protect tunnels subjected to reverse faulting - Chaofan Yao; Wang Luo; Yifei Zhang; Chuan He; Yao Li; Wenbo Yang; Yuquan Liu; Ran Yuan (Computers and Geotechnics, 2023)

One-step solvent-free approach to constructing microporous BCNO to enhance adsorptive desulfurization - Yuan Zhang; Hongshun Ran; Xinyu Liu; Xinmiao Zhang; Tianxiao Zhu; Jie Yin; Jinrui Zhang; Linhua Zhu; Jing He; Hongping Li; Huaming Li (Chemical Engineering Journal, 2023)

Modeling China's terrestrial ecosystem gross primary productivity with BEPS model: Parameter sensitivity analysis and model calibration - Xiuli Xing; Mousong Wu; Wenxin Zhang; Weimin Ju; Torbern Tagesson; Wei He; Songhan Wang; Jun Wang; Lu Hu; Shu Yuan; Tingting Zhu; Xiaorong Wang; et al. (Agricultural and Forest Meteorology, 2023)

Different Source Contributions of Bioactive Trace Metals in Sinking Particles in the Northern South China Sea - Weiying Li; Jingjing Zhang; Hongliang Li; Zezhou Wu; Xingju He; Lihua Ran; Martin G. Wiesner; Jianfang Chen (Journal of Marine Science and Engineering, 2023)
Time-series samples intercepted via three synchronized moored sediment traps, deployed at 1000 m, 2150 m, and 3200 m in the northern South China Sea (NSCS) during June 2009–May 2010, were analyzed to quantify the bioactive trace metal fluxes in sinking particles and investigate their different source contributions. Iron (Fe) primarily originated from lithogenic sources. Manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), and zinc (Zn) exhibited various degrees of enrichment over their continental crustal ratios. Since the sources of bioactive trace metals in sinking particles can be divided into lithogenic, biogenic, and excess fractions, mass conservation calculations were used to quantify the contribution of each source. The results showed that Fe, Mn, and Co had extremely low biogenic proportions (0.1–3.3%), while Ni, Cu, and Zn had higher proportions (2.7–17.3%), with the biogenic fraction decreasing with the depth. Moreover, excess sources accounted for a significant proportion of Mn (68–75%), Co (34–54%), Ni (60–62%), Cu (59–74%), and Zn (56–65%) in sinking particles at the three sampling depths. The excess fractions of Mn, Co, and Cu in sinking particles can be affected by authigenic particles. This is supported by their similar scavenging-type behavior, as observed via the increase in their fluxes and enrichment patterns with the increasing depth. Furthermore, the excess fractions of Ni, Cu, and Zn may have significant contributions from anthropogenic sources. The variability of Fe in sinking particles was mainly controlled via lithogenic matter. Notably, organic matter and opal were found to be pivotal carriers in the export of excess bioactive trace metals (Mn, Co, Ni, and Cu) via the water column, accompanied with the elevated ballast effect of lithogenic matter with the depth. However, the transportation of excess Zn was more complicated due to the intricate processes involved in Zn dynamics. These findings contribute to our understanding of the sources and transport mechanisms of bioactive trace metals in the marine environment.

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Construction and evaluation of a phospholipid-based phase transition in situ gel system for brexpiprazole - Ran Tao; Li Liu; Yingxin Xiong; Qianyu Zhang; Xiangyu Lv; Linbo He; Fang Ren; Lu Zhou; Baoyan Chen; Kexin Wu; Yan Zhang; Huali Chen (Drug Delivery and Translational Research, 2023)

Microplastic contamination in the dominant crabs at the intertidal zone of Chongming Island, Yangtze Estuary - Fengrun Wu; Tao Wang; Xueyan Li; Ran Zhao; Fengdong He (Science of The Total Environment, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Design of a novel chimeric peptide via dual blockade of CD47/SIRPα and PD-1/PD-L1 for cancer immunotherapy - Zheng Hu; Wanqiong Li; Shaomeng Chen; Danhong Chen; Ran Xu; Danlu Zheng; Xin Yang; Shuzhen Li; Xiuman Zhou; Xiaoshuang Niu; Youmei Xiao; Zhuoying He; et al. (Science China Life Sciences, 2023)

Biological carbon pump responses to multiscale physical processes: a review of sediment trap studies in the South China Sea - Jingjing Zhang; Hongliang Li; Martin G. Wiesner; Lihua Ran; Xingju He; Guangxi Chi; Xinyang Wang; Jinping Yu; Jianfang Chen (Frontiers in Marine Science, 2023)
Accurately assessing the capacity of the modern ocean to photosynthetically fix and sequester atmospheric CO 2 , termed the biological carbon pump (BCP), is a key component in studies on the marine carbon cycle and the global climate system. Particulate organic carbon (POC) flux into the ocean interior is an important indicator of the BCP strength, and it can be directly measured by sediment traps on time scales from days to years. This study has been conducted in the South China Sea (SCS) for over three decades. The SCS is one of the largest tropical marginal seas, located in the Asian monsoon region with frequent occurrence of dynamic physical processes and anthropogenic perturbations. It hosts an ideal natural laboratory to investigate the response of the BCP to multiscale physical processes. In this mini review, we briefly introduce the study history of mooring sediment traps in the SCS, synthesize the processes that regulate the temporal variability in mesopelagic POC flux, and how it is sensitive to climate changes. The time-series characteristics of the POC flux are clearly linked to primary production, as well as the key physical processes in the upper layer. The seasonal East Asian monsoon, intraseasonal eddies, aerosol deposition and interannual El Niño Southern Oscillation (ENSO) events are the main controlling factors over weekly to yearly timescales. Together, they suggest that the multiscale physical forcing in the upper layer regulates the mesopelagic POC export flux by controlling nutrient supplementation and subsequent POC production.

Bioelectret poly(lactic acid) membranes with simultaneously enhanced physical interception and electrostatic adsorption of airborne PM0.3 - Han Shang; Keke Xu; Tian Li; Hao-Ran Yang; Jiefeng Gao; Shihang Li; Jintuo Zhu; Xinjian He; Shenghui Zhang; Huan Xu; Baolong Shen (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

A relatively warm and humid Oligocene climate in the northeastern Tibetan Plateau based on a high-resolution clay mineralogical and geochemical record - Chunxia Zhang; Ran Zhang; Bin Hu; Xiaoyan Zhang; Pei Li; Ning Tan; Yunxia Jia; Zhilin He; Haibin Wu; Zhengtang Guo (Global and Planetary Change, 2023)

Controlling internal nutrients loading at low temperature using oxygen-loading zeolite and submerged macrophytes enhances environmental resilience to subsequent high temperature - Guining Wei; Jiani Xu; Bing Yang; Wei Li; Yixin He; Bingran Tang; Yongchuan Yang; Ran Cai; Xiaojun Miao; Mengzi Liu; Hong Li; Ruilin Wang (Environmental Research, 2023)

Selenium/sulfur-modified montmorillonite materials mitigate mercury pollution in farmland - Shu Ran; Tianrong He; Shengpeng Li; Deliang Yin; Pan Wu; Yiyuan Xu; Jiating Zhao (Environmental Pollution, 2023)

Digital mapping of heavy metals in urban soils: A review and research challenges - Tiezhu Shi; Li He; Ran Wang; Zhijuan Li; Zhongwen Hu; Guofeng Wu (CATENA, 2023)

Ag@Bi5O7I nanoparticles deposited on Bi(OH)3 nanosheets for boosting photocatalytic antibacterial activity under visible light irradiation - Qinghan Chen; Li Wang; Dehui He; Bo Xiao; Xia Ran; Rong Li; Hong Xu; Jian Feng (Journal of Environmental Chemical Engineering, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Natural restoration enhances soil multitrophic network complexity and ecosystem functions in the Loess Plateau - Jia He; Junhong Zhang; Jianyu Wang; Zhenghong Dong; Zexin Meng; Ran Xu; Yongbiao Ji; Yuyu Li; Jun Chen; Xuyang Qi; Xinsheng Wang; Xiuting Li; et al. (CATENA, 2023)

Remote estimation of leaf water concentration in winter wheat under different nitrogen treatments and plant growth stages - Li He; Meng-Ran Liu; Shao-Hua Zhang; Han-Wen Guan; Chen-Yang Wang; Wei Feng; Tian-Cai Guo (Precision Agriculture, 2023)

Cost-effective electric bus resource assignment based on optimized charging and decision robustness - Qiuzi Chen; Chenming Niu; Ran Tu; Tiezhu Li; An Wang; Dengbo He (Transportation Research Part D: Transport and Environment, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

In-situ reacted multiple-anchoring ligands to produce highly photo-thermal resistant CsPbI3 quantum dots for display backlights - Hongjin Li; Yun Gao; Xingjian Ying; Yifeng Feng; Meiyi Zhu; Dingshuo Zhang; Guochao Lu; Ran Tao; Qiuting Cai; Haiping He; Xingliang Dai; Zhizhen Ye; et al. (Chemical Engineering Journal, 2023)

Legal advice on the Chinese compensatory fund system for oil pollution damage caused by ships from the perspective of marine environmental governance - Ben-Chao Fu; He-Ran Li (Frontiers in Marine Science, 2023)
As one of the primary obstructive factors for marine environmental governance, the frequent occurrence of oil pollution damage caused by ships has resulted in the establishment of compensation funds, such as the Oil Spill Liability Trust Fund of the United States, Ship Oil Pollution Fund of Canada and International Oil Pollution Compensation Fund (IOPC). Frequently suffering from marine oil pollution, China has extended considerable effort in marine environmental governance. Following the introduction of the ‘green principle’ into the Civil Code, China attached increasing significance to the legislation including compensation for oil pollution damage caused by ships. China formally established a compensation fund in 2012, and the past decade has witnessed the burgeoning development of the Chinese Ship-source Oil Pollution Compensation Fund (CSOPC), in addition to several defects which impede the fund from achieving the goal of marine environmental governance. As a national fund that is independent of the IOPC, the CSOPC adopts several regulations that are distinctive from internationally recognized practice; for instance, not recognizing pure economic loss within the scope of compensation. Such unique parameters, though partially originating from the national conditions in China, have resulted in glaring defects, including incomplete compensation scope and inappropriate compensation measures. Given the above problems, this study endeavours to provide several legal recommendations from the perspective of macro policies for improving the top-level design of the system, enhancing oil pollution compensation capabilities, and promoting the internationalization process. The study proposes two potential regulatory paths for innovation; namely, enlarging the range of compensation and establishing an essential emergency fund. From the perspective of protecting the rights of the victims of oil pollution damage and safeguarding the public interests of the ocean, this study puts forward relevant legal suggestions, which are expected to make valuable contributions to improving the compensation system for oil pollution damage caused by ships in China and promoting the governance of the marine environment.

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Associations of exposure to multiple metals with the risk of age-related cataract in Anhui, China: a case–control study - Yan-Qing Li; Qian Wang; Ran Liu; Guo-Ao Li; Jia-Liu He; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Degradation of phenol by photocatalysis using TiO2/montmorillonite composites under UV light - Huijuan Li; Yeting Yao; Xiaoyan Yang; Xusheng Zhou; Ran Lei; Sufang He (Environmental Science and Pollution Research, 2022)

Risk and protection strategies of Amolops wuyiensis intestine against gastrointestinal nematode ( Cosmocercoides wuyiensis n. sp.) infection - Yilin Shu; Yunyun Xie; Shikun Li; Liming Cai; Ying Liu; Yalin Feng; Jun He; Huijuan Zhang; Menglong Ran; Qina Jia; Hailong Wu; Linming Lu (Environmental Microbiology, 2022)
Summary Anuran amphibians are susceptible to infection by intestinal nematodes, but the damage and response mechanisms that occur in their intestines after infection are only partially understood. In this study, the intestinal disruption and response mechanisms in Amolops wuyiensis frogs infected with Cosmocercoides wuyiensis n. sp. were revealed through analysis of the intestinal histopathology, digestive enzyme activity, transcriptome and intestinal microbiota. Tissue section analysis showed histological damage and inflammation in the infected intestine, and the digestive enzyme activity indicated a decrease in digestion and absorption of some nutrients. We found that infection led to differences in the intestinal microbiota composition, including lower diversity and symbiotic relationships. The greater relative abundance of the genera Burkholderia and Rhodococcus may enhance intestinal immunity to resist pathogenic infections. A comparison of the transcriptomes of infected and uninfected intestines revealed 1055 differentially expressed genes. GO enrichment and KEGG pathways analyses suggested that the guts of infected C . wuyiensis n. sp. show enhanced complement activation, cell adhesion molecule function, NOD‐like receptor signalling pathway activity and other innate immunity responses. Among the adaptive immune responses, the intestinal immune network for IgA production was significantly enriched, and the expression of IL‐17D and transforming growth factor beta‐1 genes were upregulated in the infected intestine. These results imply that C . wuyiens is n. sp. infection of A . wuyiensis intestine may trigger innate and adaptive immune responses, which reduce the post‐infection burden. Furthermore, the intestine of A . wuyiensis may also respond to C . wuyiensis n. sp. infection by increasing metallocarboxypeptidase activity and accelerating smooth muscle contraction.

Seepage field distribution and water inflow laws of tunnels in water-rich regions - Zheng Li; Zi-quan Chen; Chuan He; Chun-chi Ma; Chao-ran Duan (Journal of Mountain Science, 2022)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Terrestrial carbon cycle model-data fusion: Progress and challenges - Xin Li; Hanqing Ma; Youhua Ran; Xufeng Wang; Gaofeng Zhu; Feng Liu; Honglin He; Zhen Zhang; Chunlin Huang (Science China Earth Sciences, 2021)

Associations between essential microelements exposure and the aggressive clinicopathologic characteristics of papillary thyroid cancer - Ming-Jun Hu; Jia-Liu He; Xin-Ran Tong; Wan-Jun Yang; Huan-Huan Zhao; Guo-Ao Li; Fen Huang (BioMetals, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Effect of ambient air pollution on tuberculosis risks and mortality in Shandong, China: a multi-city modeling study of the short- and long-term effects of pollutants - Yao Liu; Shi Zhao; Yifan Li; Wanmei Song; Cuixiang Yu; Lei Gao; Jinjun Ran; Daihai He; Huaichen Li (Environmental Science and Pollution Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Prediction of methane production from co-digestion of lignocellulosic biomass with sludge based on the major compositions of lignocellulosic biomass - Pengfei Li; Chao He; Chongbo Cheng; Youzhou Jiao; Dekui Shen; Ran Yu (Environmental Science and Pollution Research, 2021)

Effects of Co-Applications of Biochar and Solid Digestate on Enzyme Activities and Heavy Metals Bioavailability in Cd-Polluted Greenhouse Soil - Shuaixing Xue; Fengfen Chen; Yuying Wang; Zhijiang Shao; Congguang Zhang; Ling Qiu; Yi Ran; Li He (Water, Air, & Soil Pollution, 2021)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Plant height and its relationship with yield in wheat under different irrigation regime - Zhenxian Gao; Yanxia Wang; Guoying Tian; Yankun Zhao; Caihua Li; Qiao Cao; Ran Han; Zhanliang Shi; Mingqi He (Irrigation Science, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

NIS and epithelial-mesenchymal transition marker expression of circulating tumor cells for predicting and monitoring the radioactive iodine-131 therapy effect in differentiated thyroid cancers - Lei Zheng; Guiyu Wang; Wei Guo; Deng Pan; Laiping Xie; Song He; Chaoxue Luo; Hongmin Li; Yaling Ran; Shiyang Wu; Fang Liu; Xiaoli Zhang; et al. (Molecular Biology Reports, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Improving the oral bioavailability of tapentadol via a carbamate prodrug approach: synthesis, bioactivation, and pharmacokinetics - Yingchao Li; Yongjun Wang; Ran Zhang; Cuiru Liu; Yue Wei; Jin Sun; Zhonggui He; Youjun Xu; Tianhong Zhang (Drug Delivery and Translational Research, 2018)

Prediction of brittleness based on anisotropic rock physics model for kerogen-rich shale - Ke-Ran Qian; Zhi-Liang He; Ye-Quan Chen; Xi-Wu Liu; Xiang-Yang Li (Applied Geophysics, 2017)

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis - Suxu He; Quanmin Wang; Shuning Li; Chao Ran; Xiaoze Guo; Zhen Zhang; Zhigang Zhou (Science China Life Sciences, 2017)

Systematic identification and characterization of miRNAs and piRNAs from porcine testes - Bo Weng; Maoliang Ran; Bin Chen; Maisheng Wu; Fuzhi Peng; Lianhua Dong; Changqing He; Shanwen Zhang; Zhaohui Li (Genes & Genomics, 2017)

Legacy effects of simulated short-term climate change on ammonia oxidisers, denitrifiers, and nitrous oxide emissions in an acid soil - Xiaoya Xu; Xiaorui Liu; Yong Li; Yu Ran; Yapeng Liu; Qichun Zhang; Zheng Li; Yan He; Jianming Xu; Hongjie Di (Environmental Science and Pollution Research, 2017)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Comparison of changes in land use and land cover in China and the USA over the past 300 years - Fanneng He; Meijiao Li; Shicheng Li; Ran Xiao (Journal of Geographical Sciences, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Magnetic field can alleviate toxicological effect induced by cadmium in mungbean seedlings - Yi-ping Chen; Ran Li; Jun-Min He (Ecotoxicology, 2011)

Bio-immobilization of Cu and Zn in recirculated bioreactor landfill - Yu-Yang Long; Li-Fang Hu; Jing Wang; Cheng-Ran Fang; Ruo He; Dong-Sheng Shen (Environmental Science and Pollution Research, 2010)